2001
DOI: 10.1063/1.1400141
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and cooperativity in three-center hydrogen bonding interactions. I. Diacetamide-X dimers (X=HCN, CH3OH)

Abstract: High level ab initio calculations are carried out on diacetamide-X ͑DA-X͒ dimers, XϭHCN, CH 3 OH. The dimers are used as model systems to investigate the energetics and cooperative phenomomena in intermolecular three-center hydrogen-bond ͑H-bond͒ interactions relative to two-center H-bond interactions. The trans-trans conformer of diacetamide is chosen as a suitable model for intermolecular three-center H bonding where one H atom is interacting with two acceptor atoms. The proton-acceptor atoms are rigidly hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…In addition to vibrational studies, 1 H NMR chemical shifts can also be used to reveal cooperative phenomena. 9 As illustrated in Table III, a three-center H-bond interaction produces an enhanced shift to lower fields of the 1 H NMR signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to vibrational studies, 1 H NMR chemical shifts can also be used to reveal cooperative phenomena. 9 As illustrated in Table III, a three-center H-bond interaction produces an enhanced shift to lower fields of the 1 H NMR signal.…”
Section: Resultsmentioning
confidence: 99%
“…3͑a͒ of Paper I. An H bond in a sixmembered ring is described in terms of r, d 1 , R 1 , and 1 . An H bond in a five-membered ring is described in terms of r, d 2 , R 2 , and 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies support the notion that intermolecular bifurcated H-bond formation is a process that gives rise to negative cooperative effects. 36,37 For intramolecular bifurcated H bonds, examples of positive and negative cooperative effects have been reported. [38][39][40] The importance of resonance-assisted hydrogen bonding ͑RAHB͒ in bifurcated hydrogen bonds was recently pointed out by Rybarczyk-Pirek et al 41 for the crystal structures of some new phosphorochromone derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…These studies support the notion that intermolecular bifurcated H-bond formation is a process that gives rise to negative cooperative effects. 24,25 For intramolecular bifurcated H bonds, examples of negative and positive cooperative effects have been reported. 26 -28 Very few studies of cooperative effects in chains of bifurcated H bonds have been reported.…”
Section: Introductionmentioning
confidence: 99%